1981
DOI: 10.1002/1097-0142(19810301)47:5+<1121::aid-cncr2820471310>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for dietary intervention studies in colon cancer

Abstract: As a result of many studies in descriptive and analytic epidemiology, in animal carcinogenesis, and in the direct examination of body fluids for mutagens/carcinogens, it is possible to develop a list of dietary factors that may be associated with the high rate of colon cancer and related cancers in Western countries. This paper is concerned with the design of intervention studies to clarify which of these factors is important. The size of such intervention trials is influenced primarily by two factors: the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This may have been a consequence of the cumbersome method that has been used to test possible interventions. The primary approach used has been randomised controlled trials in which the end point was the appearance of colonic polyps (Bruce et al, 1981). These tumours take years to develop and many subjects are needed to yield significant results.…”
mentioning
confidence: 99%
“…This may have been a consequence of the cumbersome method that has been used to test possible interventions. The primary approach used has been randomised controlled trials in which the end point was the appearance of colonic polyps (Bruce et al, 1981). These tumours take years to develop and many subjects are needed to yield significant results.…”
mentioning
confidence: 99%
“…Colorectal adenomatous polyps with abnormal cell-kinetics characteristics has been suggested to be putative precursor lesions to carcinoma (14). Bruce et al (15) and Lippmann et al (16) showed that hyperproliferation of colonic epithelium is an appropriate intermediate end-point for chemopreventive intervention.…”
mentioning
confidence: 99%
“…There has been considerable interest in the potential association of diet and colorectal cancer (Graham and Mettlin, 1979;Jain et al, 1980;Zaridze, 1981Zaridze, , 1983Bruce et al, 1981;Miller et al, 1983;McKeown-Eyssen and Bruce, 1985; Kolonel, 1987). Dietary fiber has been studied in this respect, as well as fat, protein, micronutrients, cruciferous vegetables, and other selected food groups.…”
mentioning
confidence: 99%